Content analysis of Malaysian radio and television coverage during the election of 1990 / Abdul Ghani Karim - Karim, Abdul Ghani (Faculty of Communication and Media Studies (FCMS), 1994)
The campaign for the 1990 general elections started from the nomination of candidates as from 11th October to 10th and 21st October 1990, that is the election days. A content analysis research of Malaysian radio and television coverage was undertaken during the process of election.